Significantly higher incidence of circulating fatty objects in portal blood samples compared to peripheral blood samples in patients with pancreatic ductal adenocarcinoma - Wang, Ruoxiang; Park, Kenneth; Gaddam, Srinivas; Liu, Quin; Watson, Rabindra; Lim, Adrian; Ou, Yan; Zhang, Yi; Edderkaoui, Mouad; Lewis, Michael S.; Lo, Simon K.; Pandol, Stephen J. (Frontiers in Oncology, 2025)
IntroductionWe previously reported the identification of circulating fatty objects (CFOs), abnormal entities found in peripheral blood samples from cancer patients. CFOs are large spherical objects with high contents of heavy cholesterol lipids, posing a risk of vessel embolization and circulation occlusion, common complications in clinical cancers. Initial characterization suggested that CFOs bear resemblance to bile salts, prompting further investigation into the potential link between bile and cancer-associated vascular occlusion.MethodsTo explore this connection, we analyzed portal blood samples from patients diagnosed with pancreatic ductal adenocarcinoma (PDAC), as CFOs were most frequently detected in this type of cancer (20.4% incidence). Portal vein samples were collected via transhepatic endoscopic ultrasound-guided fine-needle aspiration and treated with ammonium chloride hemolysis to facilitate enumeration and characterization of CFOs in the nucleated blood cell fraction.ResultsCFOs were observed in 14 out of the 16 portal samples, indicating a significantly higher incidence compared to peripheral samples. Despite this, portal CFOs exhibited similar characteristics to peripheral CFOs. In a parallel study, a portion of the portal samples was filtered through an Exthera’s Seraph 100 column before hemolysis, resulting in no detection of CFOs.DiscussionThese findings suggest that CFOs originate from bile. It is probable that CFOs are insoluble bile lipids that have ebbed into the portal vein and subsequently shunted to the systemic circulation due to PDAC-induced hepatobiliary system abnormalities. It appears that hemofiltration can effectively remove CFOs from circulation.